"The dream ends there": transnational feminist negotiations in Pauline E. Hopkins and Olive Schreiner - Barends, Heidi (Department of English Language and Literature, 2019)
This dissertation investigates the African American writer, Pauline E. Hopkins (1859-1930), and the white South African writer, Olive Schreiner (1855-1920). Although Hopkins and Schreiner wrote at the same time, inhabited settler-colonial contexts (the United States and South Africa) that can in many respects be seen as similar, and shared an investment in gender and race activism, they are rarely associated with each other. This thesis examines the connections between them, illuminating a historical moment in which a transnational feminism was both in the making and a historical impossibility. Drawing from Schreiner’s and Hopkins’s literary work and archives, I use transnational feminist analysis, literary analysis, and feminist and black feminist theory to interrogate the ways in which these two writers defined, endorsed and contested the notion of female solidarity. I trace the authors’ thoughts on race, class and gender over the course of their lives, examining the historical moment of their connections in the light of their nonfiction and fiction. I conclude that, while never meeting, Hopkins and Schreiner moved in similar transnational and cross-racial circles, a symptom of both the possibilities and impossibilities of transnational and cross-racial solidarity. Their non-fiction lays bare the frictions between black and white women in the United States and South Africa; on the other hand, the imaginative capacity of their fiction offered both Hopkins and Schreiner a space in which to tease out these conflicts and to expand their feminist visions. Without promoting any notion of universal sisterhood, I argue that viewing Hopkins and Schreiner in tandem underscores their connectedness. Both authors made attempts to bridge the contemporary social divisions between women in service of a more inclusive feminist project. Attempt is the operative word, for neither writer was able to conceive of such a feminist project in its entirety. Nevertheless, their efforts to do so demonstrate the affinities that may exist between figures conventionally considered to be socially separated; they also emphasise the political urgencies of a transnational feminism, urgencies that I propose extend into our present.